ANALISIS FUNDAMENTAL MENGGUNAKAN RETURN ON EQUITY (ROE), EARNING PER SHARE (EPS), PRICE EARNING RATIO (PER), PRICE TO BOOK VALUE (PBV) DAN DIVIDEND YIELD (DY) SEBAGAI DASAR KEPUTUSAN INVESTASI - Muhammad Romy Saputra; Roza Linda (Yayasan Azam Insan Cendikia, 2023)
This research was conducted at a coal mining company listed on the Indonesia Stock Exchange. The purpose of this study is to make decisions in investing in the coal mining sub-sector. This research is a quantitative descriptive research. The data used in this study is secondary data by taking a sample of 6 issuers. Sampling was done by purposive sampling technique. The research location is a coal mining company listed on the Indonesian Stock Exchange. Based on the research results, the results of this study resulted in 27 recommendations for investment decisions in the coal mining sub-sector in the 2016-2020 period. The author recommends choosing two of the six samples, namely ADRO and BSSR shares because based on their fair prices ADRO and BSSR are still very low and as long term stocks and coal mining companies it is very possible for ADRO and BSSR to have even higher prices.